Aquaponics In Improving The Economy And Food Security Of Urban Communities In South Meruya - Utami, Fransisca Listyaningsih; Feriyanto, Dafit; Oktasari, Dian Primanita (Universitas Mercu Buana, 2025)
The application of aquaponics in South Meruya has dual benefits, both in terms of improving the community's economy and food security, which ultimately improves the welfare and quality of life of urban communities. Aquaponics is an integrated system between fish farming and hydroponic farming that utilizes fish waste as nutrients for plants and filters the water that is reused for fish. The application of freshwater fish aquaponics in South Meruya is an innovative solution to address economic challenges and food security for urban communities. Aquaponics assists communities in generating fresh revenue by producing fish and vegetables for local markets. The relatively low operational costs and limited space make aquaponics ideal for implementation in urban areas with limited land, such as in South Meruya. Aquaponics allows communities to produce food independently and sustainably. Community food security increases due to easier access to sources of protein and fresh vegetables.